The Knowledge of Lung Tuberculosis Suspects for Sputum Examination Attitude In The Kamoning Primary Health Care - Puteri Febriana Arivany (Universitas Airlangga, 2017)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium Tuberculosis bacteria. Pulmonary TB is a contagious disease that mostly attacks the lung organs but does not rule out the possibility of attacking other organs. Sputum examination is one of the efforts to establish TB diagnosis and determine the potential for transmission. This study aims to determine the relationship of respondents' knowledge with actions in sputum examination at the Primary Health Care / Public Health Center (PHC) of Kamoning, Sampang District in 2015. This study uses observational analytic research with survey methods and cross-sectional approaches. The study was conducted on 60 patients and the method of sampling using simple random sampling. The independent variable is education, occupation, respondent's income, education, and respondent's attitude in conducting sputum examination. The dependent variable is an action in conducting sputum examination. Data collection instruments used were online health center data, patient medical records, and questionnaires. The results showed that the contingency coefficient of knowledge of respondents suspected of pulmonary TB in sputum examination was 0.253 and OR = 3.600. The conclusion is that there is a weak relationship between respondents' knowledge and actions in conducting sputum examination. Symptoms and treatment of pulmonary TB can be known if health workers work together with religious leaders and community leaders to provide information according to the age and education of respondents.